Fabrication of supersaturated Cu-Sn alloy sheets and their antibacterial properties - Shin, J. H.; Park, J. S.; Bae, D. H. (Metals and materials international, 2011)
Supersaturated Cu-Sn alloy sheets were successfully fabricated by hot-rolling mechanically alloyed (MAed) nanocrystalline powders within a range of up to 22 wt.% of Sn, and their antibacterial and ionization properties were investigated. While the pure Cu and hot-rolled Cu-Sn sheets using MAed powders show excellent antibacterial properties, the corrosion potential of the hot-rolled Cu-Sn using MAed powders is much less than that of the as-cast Cu-Sn and decreases as the Sn content increases, implying that the hot-rolled Cu-Sn alloy sheets using MAed powders have a more effective antibacterial property, mainly due to supersaturation.